The Climate of Palestine in Palestinian Proverbs A Study in Folk Geography (Journal of Libya for geographical studies, 2024)
Our ancestors in Palestine, and before the development of weather monitoring systems, stations, and their scientific data, relied on a system of popular proverbs that describe the state of the weather in each of the seasons and every month of the year, as this study sought to collect and archive the largest possible number of popular proverbs related to the weather and climate of Palestine, and interpreting its meanings in a scientific way, and linking it to the climatic geography of Palestine, and to the folkloric geography, in order to preserve this original cultural heritage from loss and extinction, and in a serious attempt to transfer it to subsequent generations, and by following the descriptive and analytical approach. For a group of weather conditions, which are represented by depressions, air elevations and air masses, and that the Palestinian farmer has cumulative experimental experience in extrapolating, monitoring and describing weather conditions and linking them to the movement of stars and to natural climatic phenomena such as lightning, thunder, rainbows, winds, clouds, etc. and how to take them as a time reference from year to year. The study recommended the need to preserve Our popular Palestinian proverbs by recording and archiving them through studies, books, literature, articles and encyclopedias, and promoting studies related to the folklore geography of Palestine
Keywords: Palestine; popular proverbs; climate; folk geography